Antipyretic Drug Candidates Through Reverse Docking Techniques Used In Science Learning - Muhamad Iksan; Frida M Yusuf; Fitriani Fitriani B; Wa Ode Al Zarliani (Postgraduate, University of Mataram, 2023)
Red ginger (Zingiber officinale var. Rubrum) is a commonly used rhizome known for its fragrant and spicy taste. It contains gingerol and shogaol compounds that have antipyretic effects by inhibiting prostaglandin formation and stimulating the production of interleukin-10, an endogenous antipyretic. This study aimed to evaluate the potential of gingerol and shogaol compounds as antipyretic drug candidates through reverse docking techniques targeting interleukin-10 (IL-10). Ten natural compounds from red ginger were predicted for their potential as antipyretic drugs and docked with the IL-10 receptor protein using various computer programs. The molecular docking results showed that (6)-shogaol had four amino acid bond residues that were the same as the ibuprofen control compound, indicating its potential as an antipyretic drug candidate. Furthermore, (6)-shogaol had the same binding affinity as the control compound and was safe for oral consumption based on pharmacokinetic and toxicity tests using Lipinski's Rule, Toxtree, and admet-T. These findings suggest that (6)-shogaol is a promising antipyretic drug candidate compared to other compounds. In conclusion, this study identified the potential of (6)-shogaol as an antipyretic drug candidate through reverse docking techniques targeting interleukin-10. Red ginger could provide a natural alternative for antipyretic drugs, and further research is recommended to explore the role of gingerol and shogaol compounds in targeting other proteins